Determinants of public-private partnerships in infrastructure in Asia: Implications for capital market development - Hyun Suk; Donghyun Park; Shu Tian (Asian Development Bank (ADB), 2018)
In this study, we attempt to understand the role of greater access to finance, i.e., stocks, bonds, and bank loans, in public-private partnership (PPP) investment in developing countries. Most developing countries still depend heavily on fiscal financing for infrastructure projects. Our empirical results reconfirm the fact that banks remain the major source of finance for infrastructure projects. The domestic bond market should be further developed to have depth and liquidity enough to provide longterm funding for private sector investors. Interestingly, we find a negative impact of bond market development on PPP investment. A possible interpretation is that financing through government bonds, which dominates bond markets in developing countries, discourages private sector participation by reducing financing access to the corporate bond market. Our evidence underlines the importance of a well-functioning corporate bond market in developing countries, which can offer long-term financing to private sector participation in infrastructure investments.
Keywords: E20; G10; H00; 330; bond market development; government bond; public-private partnership